The Borax Test Using Purple Sweet Potatoes (Ipomoea batatas Var. Ayumurasaki) Extract on Meatball Samples in Banyuwangi District 2022: Uji Boraks Menggunakan Ekstrak Ubi Jalar Ungu (Ipomoea batatas Var. Ayumurasaki) pada Sampel Bakso di Kecamatan Banyuwangi 2022 - Citra Aisyah; Azmi Prasasti; Stephanie Devi Artesimia (Journal Pharmasci (Journal of Pharmacy and Science), 2023)
Borax or sodium biborate is a white crystalline compound that is stable at room temperature. Ii is usually used to make detergents and antiseptics. However, nowadays there is still a lot of borax added to food ingredients to make food chewier, such as tofu, wet noodles, meatballs, ​​chicken, fresh and salted fish. Purple potatoe (Ipomoea batatas Var. Ayumurasaki) has fairly high anthocyanin content, 5.92-402 mg/25 mg of fresh purple potato. Anthocyanins are compounds that are able to detect the presence of borax in food samples because they can break down borax bonds into borax acid by binding it to a blue color. This study aimed to determine the presence of borax in meatball samples in Banyuwangi district using purple potato extract with the maceration and pressing method, then a comparative test was carried out using the test kit method for valid results. The positive control used was borax with a level of 0.02 mg/2 ml, and the negative control used aquadest. The maceration method produced a significant color change when compared to other method, namely bluish green when interacting with borax. The meatball samples in Banyuwangi sub-district showed that all samples were free from borax, this was indicated by the absence of a color change when interacting with the purple sweet potato or the test kit.